ABVD DOES NOT FIT ALL ADVANCED-STAGE CLASSICAL HODGKIN LYMPHOMA PATIENTS: REAL-WORLD FIVE-YEAR SINGLE-CENTER EXPERIENCE - Vuković, Vojin; Karan-Djurasevic, Teodora; Bibic, Tamara; Kozarac, Sofija; Ivanovic, Jelena; Tulic, Pavle; Lekovic, Danijela; Antic, Darko (Srpski medicinski časopis Lekarske komore, 2024)
Introduction/Aim: Advanced-stage classical Hodgkin lymphoma (AScHL) is a therapeutic challenge due to chemoresistance. This study aims to present real-world data on the application of the ABVD regimen (doxorubicin, bleomycin, vinblastine, dacarbazine) in patients with AScHL.Methods: This retrospective study examines the clinical and laboratory parameters, as well as the treatment and outcome of patients diagnosed with AScHL, in the period between 2016 and 2020.Results: The cohort consisted of 49 patients with AScHL. Median follow-up was 47 months (range: 1 – 79). The most important clinical and laboratory characteristics are summarized in Table 1.All patients were initially treated with ABVD. The overall response rate was 72.3% (complete response = 61.7%; partial response = 10.6%), while 27.7% of patients exhibited refractoriness. Additionally, 10.6% relapsed at a later stage. Of the investigated parameters (Table 1), only an elevated erythrocyte sedimentation rate (ESR) ≥ 50 mm in the first hour) was associated with shorter progression-free survival (PFS), (median PFS = 19 months vs. not reached (NR), in patients with ESR < 50 mm in the first hour; p = 0.039), while the presence of bulky disease was associated with shorter overall survival (OS), (p = 0.044). Also, refractory patients had significantly shorter OS (median OS = 54 months vs. NR in patients who achieved remission; p = 0.004). The median PFS and OS were not achieved; four-year PFS and OS were 61% and 89%, respectively. Patients treated with autologous transplantation (AT) in relapsed/refractory disease had a longer PFS (p = 0.02), but not a longer OS. Brentuximab vedotin (BV) was successfully used in 4/14 patients, of whom three patients received it as consolidation treatment after AT.Conclusion: A significant number of patients with AScHL cannot be cured with ABVD, thus more intensive treatment or innovative therapies are warranted.
Keywords: advanced-stage Hodgkin lymhoma; ABVD; survival; autologous transplantation